Fall risk prediction model for older men and women based on ambulat ambulatory physical activity le y physical activity level - A cr el - A cross-sectional population- oss-sectional populationbased study from the Oporto Region - Paulo Jorge QUINTELA CARDOSO-CARMO; Adjane Maria PONTES CÉSAR; Manuel Rubim Silva SANTOS; Maria Joana Mesquita Barbosa DE CARVALHO (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. Falls among the elderly are an important community health problem due to its high incidence, functional and social repercussion. Dissimilar results arose in recent studies concerning fall risk and physical activity levels. This study measures the association between physical activity (PA) levels, and fall risk (FR), investigates which levels of PA are influential in FR and presents a fall risk prediction models for the elderly. Material and Methods. One hundred and seventy elderly adults (72.34 ± 6.70 years old, 124 female), completed Performance-Orientated-Mobility-Assessment; PA was assessed by accelerometry. Pearson's correlation verified the association between FR, Age, and PA. Multiple linear regression (MLR) was used to investigate the influence of variables on FR. Results. PA, age are predictors of FR, with PA (moderate, negative) age (moderate, positive). MLR analysis showed FR variability explained by PA (42.0%) and by age (37.0%), and by gender, female FR explained by light PA (47.0%), while in male, FR explained by sedentary behaviour (44.1%) and age (22.7%) independently. Conclusion. Individuals with higher physical activity have lower fall risk. Older are prone to fall. Older women with light physical activity are less likely to fall. Older men with more sedentary behaviour are prone to fall.